2015
DOI: 10.1097/jcp.0000000000000345
|View full text |Cite
|
Sign up to set email alerts
|

Adjunctive Minocycline in Clozapine-Treated Schizophrenia Patients With Persistent Symptoms

Abstract: Objective Clozapine is the most effective antipsychotic for treatment refractory people with schizophrenia, yet many patients only partially respond. Accumulating preclinical and clinical data suggest benefits with minocycline. We tested adjunct minocycline to clozapine in a 10 week, double blind placebo-controlled trial. Primary outcomes tested were positive and cognitive symptoms, while avolition, anxiety/depression and negative symptoms were secondary outcomes. Methods Schizophrenia and schizoaffective pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
73
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 88 publications
(86 citation statements)
references
References 66 publications
(65 reference statements)
5
73
0
3
Order By: Relevance
“…6 Subsequent clinical studies reported efficacy of minocycline especially in alleviating negative symptoms of schizophrenia when used as add-on therapy in combination with classical antipsychotics. [7][8][9] These findings are in line with antipsychotic-like effects of minocycline in animal models of schizophrenia, demonstrating, similar to haloperidol, improvement of the cognitive deficits induced by the NMDA receptor (NMDAR) antagonist MK-801. 10 Alleviation of protracted schizophrenia-like abnormalities (hyperlocomotion, sensorimotor gating, and social interaction deficits) by minocycline was described also in a mouse model of maternal immunization.…”
supporting
confidence: 68%
“…6 Subsequent clinical studies reported efficacy of minocycline especially in alleviating negative symptoms of schizophrenia when used as add-on therapy in combination with classical antipsychotics. [7][8][9] These findings are in line with antipsychotic-like effects of minocycline in animal models of schizophrenia, demonstrating, similar to haloperidol, improvement of the cognitive deficits induced by the NMDA receptor (NMDAR) antagonist MK-801. 10 Alleviation of protracted schizophrenia-like abnormalities (hyperlocomotion, sensorimotor gating, and social interaction deficits) by minocycline was described also in a mouse model of maternal immunization.…”
supporting
confidence: 68%
“…A meta‐analysis of four of the trials documented its superiority to placebo in mitigating negative but not positive symptoms of schizophrenia . Evidence from clinical trials in individuals with schizophrenia also provides support for the hypothesis that adjunctive minocycline may improve cognitive function in individuals with BD . The open‐label study herein aimed to provide ‘proof‐of‐concept’ evidence that mitigating inflammation with adjunctive minocycline alleviates symptoms of depression and improves cognitive function in individuals with BD.…”
Section: Introductionmentioning
confidence: 84%
“…Results from a 6‐week, open‐label study suggest that adjunctive minocycline mitigates depressive symptom severity in individuals with major depressive disorder who present with psychotic features . The potential benefit of adjunctive minocycline for individuals with BD is buttressed by five randomized, placebo‐controlled trials in individuals with schizophrenia . A meta‐analysis of four of the trials documented its superiority to placebo in mitigating negative but not positive symptoms of schizophrenia .…”
Section: Introductionmentioning
confidence: 99%
“…In cuprizone-fed C57BL/6 mice, minocycline reduced microglial activation and demyelination in the brain and prevented disturbances in motor coordination (Pasquini et al, 2007;Skripuletz et al, 2010;Tanaka et al, 2013). Furthermore, minocycline in combination with an antipsychotic such as risperidone, olanzapine, quetiapine, or clozapine significantly improved positive, negative, and cognitive symptoms in recent-onset or chronic schizophrenia patients (Levkovitz et al, 2010;Ghanizadeh et al, 2014;Chaves et al, 2015;Kelly et al, 2015). From these results, it is likely that application of minocycline can dampen M1 signaling, subsequently resulting in skewing of M2a microglia that reduce proinflammatory signaling and increase production of anti-inflammatory cytokines.…”
Section: Pharmacological Approach To Neuroinflammation In Asd and Schmentioning
confidence: 99%